An MDA Approach to Business Process Model Transformations - Argañaraz, Mauro (2010)
We present in this work an MDA approach for the definition of transformations for business process models. These transformations are based on the use of two platform independent workflow universal languages –UML 2.0 Activity Diagrams and BPMN– and a platform specific language, the XPDL language. The first two languages are used in the definition of a horizontal transformation, while BPMN and XPDL are used in the definition of a vertical transformation. Although there are several options for a model transformation language, we have adhered to one of the principles of MDA, namely the use of standards, therefore adopting the QVT language, which is the transformation language proposed by the OMG. We also show, in this work, a practical case of an application of the transformations proposed here.